Endothelial plasmalemmal vesicles have a characteristic striped bipolar surface structure (The Rockefeller University Press, 1985)
Capillary endothelial cells have a large population of small (65-80 nm diameter in transmission electron microscopy) vesicles of which a large fraction is associated with the plasmalemma of the luminal and abluminal side. We studied the fine structure and distribution of these plasmalemmal vesicles by high resolution scanning electron microscopy in cultured endothelial cells obtained from bovine adrenal cortical capillaries. Cell monolayers were covered with polylysine-coated silicon chips, split in high potassium buffer, fixed in aldehyde mixtures, and then treated with OsO4 and thiocarbohydrazide. After critical point drying, the specimens were coated with a thin (less than 2 nm) continuous film of chromium. On the cytoplasmic aspect of the dorsal plasmalemmal fragments seen in such specimens, plasmalemmal vesicles appear as uniform vesicular protrusions approximately 70-90 nm in diameter, preferentially concentrated in distinct large fields in which they occur primarily as single units. Individual plasmalemmal vesicles exhibit a striped surface fine structure which consists of ridges approximately 10 nm in diameter, separated by furrows and oriented as meridians, often ending at two poles on opposite sides of the vesicles in a plane parallel to the plasmalemma. This striped surface structure is clearly distinct from the cage structure of coated pits found, at low surface density, on the same specimens. The cytoplasmic aspect of the plasmalemma proper is covered by a fibrillar infrastructure which does not extend over plasmalemmal vesicles but on which the latter appear to be anchored by fine filaments.